Modelagem de efeitos plasmônicos em um metamaterial nanoestruturado para aplicação em sensoriamento óptico - SILVA, Anderson Oliveira (Universidade Federal do Pará, 2014)
Metamateriais are artificial media structured to obtain physical properties not readily found in nature. In general, these media are arranged periodically with a unit cell whose dimensions are smaller than the wavelength of the incident electromagnetic radiation. This characteristic allows dealing with such materiais as homogenized media, which means describing them by effective constitutive parameters. This work performs the analytical and numerical model of a metamaterial structured with metallic inclusions. It is implemented a formalism based on the Maxwell-Garnett approach in order to describe the effective refraction index of the metamaterial accounting for the geometry of the nanoparticles and the nature of excited local field modes. It is shown that these modes correspond to surface plasmon excitations. From the characterization of the metamaterial at the optical domain, it is investigated the potential of such medium to the construction of more compact refraction index sensors, with sensitivity values higher than the ones typically found in systems based exclusively on optical fibers.